The Effect of Emotional Intelligence Training Program on Social and Academic Adjustment Among First Year Jordanian University Students - Jdaitawi, Malek Turki (2012)
The purpose of this study is to identify the effect of an emotional intelligence training programme in increasing the level of emotional intelligence, and its effect on the level of social and academic adjustment among first year students in two universities in the north of Jordan. Using the 2x2~3fa ctorial design, the quasi experimental quantitative study examined three factors which are training group, gender and age. The sample size used for this research consisted of 289 first year students (148 males and 141 females) who voluntarily participated in this study and they were randomly assigned to two groups. The participants involved in the skilled emotional intelligence training group were given nine sessions within the duration of ten days. Participants in the controlled group were not given any training. Six trainers administrated the training sessions in which two highly reliable and valid instruments were used to measure the research variables. The instruments were the Emotional Intelligence Appraisal (EIA), and the Student Adjustment to College Questionnaire (SACQ). The multivariate analyses (MANOVA, Repeated Measure ANCOVA, MANCOVA, and Pearson Correlation) were used to test the research hypotheses at the significant level of p <.05. The multivariate analysis of covariance and the Repeated Measure ANCOVA showed that the training was significantly effective in improving the level of emotional intelligence, but the improvement for social and academic adjustment was not significant. The results also found that the male group showed better overall scores in emotional intelligence, but the differences were not significant. Moreover, the results were also not significant among the three age groups. Finally, there were profound interactions between skilled emotional intelligence, gender and age. Therefore, intervention programmes for this particular population are recommended.